2011
DOI: 10.1002/lary.21791
|View full text |Cite
|
Sign up to set email alerts
|

The cochleovestibular nerve identified during auditory brainstem implantation in patients with narrow internal auditory canals: Can preoperative evaluation predict cochleovestibular nerve deficiency?

Abstract: Visualization on MRI and detection of auditory responses suggested the presence of a CVN in patients with narrow IACs; however, the possibility of the presence of a CVN should be considered even when there is no clear evidence of a CVN on preoperative evaluations. Therefore, physicians should be prudent when determining candidacy for cochlear implantation or auditory brainstem implantation in patients with narrow IACs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Currently, in smaller series, MRI imaging and electrophysiology are not predictive of outcome with CI, with many reports of children performing sufficiently with CI in these cases to avoid ABI. (31,32)…”
Section: Discussionmentioning
confidence: 99%
“…Currently, in smaller series, MRI imaging and electrophysiology are not predictive of outcome with CI, with many reports of children performing sufficiently with CI in these cases to avoid ABI. (31,32)…”
Section: Discussionmentioning
confidence: 99%
“…8,[13][14][15] Beyond this report, few studies, however, have directly addressed imaging necessary to stratify CI and ABI candidates. [16][17][18] Based on our findings, this study raises questions about variable diagnostic utility of MRI scans using reconstructed images.…”
Section: Discussionmentioning
confidence: 71%
“…Prior imaging research in sensorineural hearing loss has focused on the classification of cochlear malformations, with some groups attempting to correlate imaging findings with cochlear implant outcomes . Beyond this report, few studies, however, have directly addressed imaging necessary to stratify CI and ABI candidates . Based on our findings, this study raises questions about variable diagnostic utility of MRI scans using reconstructed images.…”
Section: Discussionmentioning
confidence: 83%
“…However, there are limitations in reliable detection of hypoplastic nerves with a diameter of 0.2-0.6 mm (as measured in six individuals with hypoplastic nerves [13]). Accordingly, hypoplastic nerves may be overlooked on MRI scans, as Song et al [14] demonstrated in six patients who underwent ABI implantation. The small nerves were clearly visible intraoperatively, whereas they were missed when preoperative MRI was used with a DRIVE sequence with a FOV of 150 mm and matrix of 256.…”
Section: Hypoplasia and Aplasia Of The Vestibulocochlear Nerve (Vcn)mentioning
confidence: 99%